A new potential energy surface for the ground electronic state of the LiH2 system, and dynamics studies on the H(2S) + LiH(X1Σ+) → Li(2S) + H2(X1Σg+) reaction. Issue 17 (7th May 2015) - Yuan, Jiuchuang; He, Di; Chen, Maodu
<x xml:space="preserve">Abstract</x> A new potential energy surface of the LiH2 system is obtained using a neural network method based on high-level energies.